Komodifikasi Nilai Keislaman Pada Poster Produk Sahaja (Analisis Semiotika Roland Barthes) - Serin Himatus Soraya (RETORIKA : Jurnal Kajian Komunikasi dan Penyiaran Islam, 2023)
Sahaja product posters contain Islamic religious symbols to attract buyers. By using the semiotic analysis of Roland Barthes' model, this study aims to describe the myth of Islamic values ​​contained in the Sahaja product poster. The analysis is done by finding a set of signs of Islamic values ​​in the poster, then analyzed based on the significance of the first level and the second level of significance. From the analysis stage, it then produces myths that are attached to Sahaja product. The commodification of Islamic values ​​is done by incorporating Islamic symbols and teachings of Islam in posters. The results of the study indicate that the Islamic values ​​contained include: first, the affirmation that Islam teaches cleanliness. Second, raise your hand when praying. Third, kindness or concern for others will flow and lead to happiness. Fourth, Sahaja product supports zakat and alms. Fifth, maintaining cleanliness means maintaining health.